A preliminary examination of the role of psychotherapist fidelity on outcomes of cognitive processing therapy during an RCT for military sexual trauma-related PTSD. Issue 1 (2nd January 2018) - Holder, Nicholas; Holliday, Ryan; Williams, Rush; Mullen, Kacy; Surís, Alina
Abstract: While cognitive processing therapy (CPT) is an effective evidence-based treatment for many veterans with military-related post-traumatic stress disorder (PTSD), not all veterans experience therapeutic benefit. To account for the discrepancy in outcomes, researchers have investigated patient- and research design-related factors; however, therapist factors (e.g. fidelity) have received less attention. The present study is a preliminary examination of the effect of psychotherapists' fidelity during CPT on clinical outcomes during a randomized clinical trial (RCT) for military sexual trauma-related PTSD. PTSD symptoms, trauma-related negative cognitions (NCs), and depression symptoms were assessed for 72 participants at baseline, and 1-week, 2-month, 4-month, and 6-month posttreatment. Of the four CPT therapists, two were found to have significantly poorer (i.e. "below average") treatment fidelity scores compared to the other two therapists who had "good" treatment fidelity scores. To examine possible therapist effects on outcomes, hierarchical linear modeling was utilized with therapist fidelity entered as a Level 2 predictor. Participants treated by a therapist with "good" treatment fidelity experienced significantly greater reductions in PTSD symptoms, NCs, and depression symptoms than patients treated by a therapist with "below average" treatment fidelity. Our preliminary findings highlight the importance of monitoring, maintaining, and reporting fidelity in psychotherapy treatment RCTs.